Barron's IELTS : - Lougheed, Lin (Barron's Educational Series, 2013)
The IELTS test is used as a measure of English language proficiency by over 7,000 educational institutions, government departments and agencies, and professional organizations in 135 countries. This updated manual for ESL students covers all parts of the IELTS and all of its question types: multiple-choice, short answer, sentence completion, flowchart completion, graphs, tables, note taking, summarizing, labeling diagrams and maps, classification, matching, and selecting from a list.